Solvent‐Influenced Fragmentations in Free‐Standing Three‐Dimensional Covalent Organic Framework Membranes for Hydrophobicity Switching. (19th February 2022) - Mohammed, Abdul Khayum; Al Khoori, Ayesha A.; Addicoat, Matthew A.; Varghese, Sabu; Othman, Israa; Jaoude, Maguy Abi; Polychronopoulou, Kyriaki; Baias, Maria; Haija, Mohammad Abu; Shetty, Dinesh
Abstract: The ordered open organic frameworks membranes are attractive candidates for flow‐assisted molecular separations. The physicochemical properties of such membranes mostly depend on their selectively chosen functional building blocks. In this work, we have introduced a novel concept of functional switchability of three‐dimensional covalent organic framework (3D‐COF) membranes through a simple solvent‐influenced fragmentation method. This room‐temperature interfacial synthesis provides free‐standing 3D‐COF membranes with distinct physicochemical properties from the same building monomers. Notably, the change of solvent from chloroform to ethyl acetate switches the membrane property from hydrophilic (water contact angle 60°) to hydrophobic (water contact angle 142°) nature. The hydrophobic 3D‐COF membrane selectively passes oil molecules from an oil–water emulsion with a gravitational flux of 1536 L m −2 h −1 . Abstract : A novel pre‐synthetically controlled framework growth strategy to tune the hydrophobicity of the 3D‐COF membranes without changing the building blocks or post‐synthetic modifications is demonstrated. The hydrophobic 3D‐COF membrane was utilized for the demulsification of an oil–water mixture.